ARNI vs ACE Inhibitors in Improving Left Ventricular Geometry, Diastolic Function, and Cardiac Power Output in HFrEF Patients: A Prospective Cohort Study among Acehnese, Indonesia - Taufiqurrahman; Teuku Heriansyah; Adi Purnawarman; Novita; Zulkarnain (Postgraduate, University of Mataram, 2025)
Heart failure with reduced ejection fraction (HFrEF) is a condition associated with high morbidity and mortality. Changes in left ventricular geometry, diastolic function, and cardiac power output (CPO) are key indicators in the management of heart failure. ARNI and ACE inhibitors have been proven effective to treat this condition, but comparative studies on these therapies in the Asian population remain limited. This study was conducted to assess changes in left ventricular geometry, diastolic function, and CPO in heart failure patients following ARNI therapy compared to ACE inhibitors among Indonesian. This observational study employed a prospective cohort design involving 73 heart failure patients divided into two groups: the ARNI group and the ACE inhibitor group. Evaluations were conducted at first admission/recruitment and after three months period of therapy using echocardiography to assess parameters of left ventricular geometry (LVMI and RWT), diastolic function (E/e' ratio), and CPO. The use of ARNI or ACE inhibitors over three months showed a significant reduction in LVMI, accompanied by an improvement in diastolic function marked by a significant decrease in the E/e' ratio (p < 0.05). However, no significant differences were observed between the two groups. CPO values increased in both groups with a p-value < 0.05, where ARNI therapy showed a greater improvement compared to ACE inhibitors (p = 0.048). The use of ARNI and ACE inhibitors in heart failure patients can improve CPO, left ventricular geometry, and diastolic function, with ARNI therapy providing a better enhancement in CPO compared to ACE inhibitors.